POPULISME DAN KEBIJAKAN LUAR NEGERI DI INDONESIA - Imelda Masni Juniaty Sianipar (Andalas Journal of International Studies (AJIS), 2015)
On October 20, 2014, Joko Widodo or familiarly known as Jokowi was sworn in as the Seventh President of the Republic of Indonesia. The majority of Indonesian society supports Jokowi because He is simple, honest and populist. The presence of populist leaders in international politics often attracts the attention of Western countries, particularly the United States. Populist leaders are often considered as the authoritarian leaders, anti-democratic, anti-Western, anti-foreign and anti-market. Hugo Chavez from Venezuela and Mahmoud Ahmadinejad from Iran are the examples. Chavez and Ahmadinejad are considered as threats by the United States because they challenge the United States led regional and global order. This article will examine the direction of Jokowi’s foreign policy. This article argues that Jokowi is a moderate populist leader. Jokowi is friendly to other countries including the West but still prioritize the national interests. Thus, Indonesia under Jokowi is not a threat to other countries and the West. In fact, they can work together to achieve their common national interests. Keywords: populism, foreign policy, Indonesia, jokowi, moderate populism